The Single Particle Level Density Calculations for Th 232 90 Using Equidistant Space Model (ESM) and NON-ESM in Fermi Gas Model - Jasim, Mahdi; Dakhil, Z.; Ahmed, Rasha (Iraqi Journal of Science, 2023)
The single-particle level densities for Th 23290 , at certain exciton number, arecalculated in terms of Equidistant Space Model, ESM, and NON-ESM, of FermiGas Model. It is found that the single particle level density, g, has no longer aconstant value and becomes an energy dependent on the contrary with NON-ESM.The finite depth of the nuclear well and pairing corrections are examined withbehavior of the single level density for both models. The particle-hole state densityhas been calculated, by means of the energy dependence of excited particles andhole level densities, for one and two fermions systems and different exciton numberin Th 23290 . The present results are compared between two models with and withoutthe inclusion of the finite well depth correction. NON-ESM system has a majoreffect in the present calculations at high excitation energies.